The innovator's solution : creating and sustaining successful growth - Christensen, Clayton M.; Raynor, Michael E.. (Mumbai: Harvard Business School Press India Limited, 2003)
"A seminal work by bestselling author Clayton M. Christensen, now with a refreshed package. In the international bestseller The Innovator's Dilemma, Clayton Christensen exposed the Achilles' heel of many companies: by ignoring the disruptive technologies that evolve to displace them, they help initiate their own demise. In The Innovator's Solution, Christensen and Michael Raynor take the idea of disruption one step further--explaining how companies can and should become disruptors themselves. Now with a new look, The Innovator's Solution proves just how timely and relevant these ideas continue to be in today's hyper-accelerated business environment. Christensen (author of the award-winning Harvard Business Review article, "How Will You Measure Your Life?"), and Raynor give usable advice on the business decisions crucial to achieving truly disruptive growth and propose guidelines for developing your own disruptive growth engine. Citing in-depth research and theories tested in hundreds of companies across many industries, The Innovator's Solution is an important addition to any innovation library and an essential read for entrepreneurs and business builders. Published by Harvard Business Review Press. "--
"A seminal work by bestselling author Clayton M. Christensen. In his international bestseller The Innovator's Dilemma, Clayton M. Christensen exposed this crushing paradox behind the failure of many industry leaders: by placing too much focus on pleasing their most profitable customers, these firms actually paved the way for their own demise by ignoring the disruptive technologies that aggressively evolved to displace them. In The Innovator's Solution, Christensen and coauthor Michael E. Raynor help all companies understand how to become disruptors themselves. Clay Christensen (author of the award-winning Harvard Business Review article, "How Will You Measure Your Life?") and Raynor not only reveal that innovation is more predictable than most managers have come to believe, they also provide helpful advice on the business decisions crucial to truly disruptive growth. Citing in-depth research and theories tested in hundreds of companies across many industries, the authors identify the processes that create successful innovation--and they show managers how to tailor their strategies to the changing circumstances of a dynamic world. The Innovator's Solution is an important addition to any innovation library"--
Includes bibliographical references and index.
Keywords: Creative ability in business; Industrial management; Customer services; Success in business; Disruptive technologies; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / Decision-Making & Problem Solving